Poverty impacts of a WTO agreement : synthesis and overview - Hertel, Thomas W., 1953- 1953- (Policy research working paper, 2005)
"This paper reports on the findings from a major international research project investigating the poverty impacts of a potential Doha Development Agenda (DDA). It combines in a novel way the results from several strands of research. Intensive analysis of the DDA Framework Agreement pays particularly close attention to potential reforms in agriculture. The scenarios are built up using newly available tariff line data and their implications for world markets are established using a global modeling framework. These world trade impacts, in turn, form the basis for 12 country case studies of the national poverty impacts of these DDA scenarios. The focus countries include Bangladesh, Brazil (two studies), Cameroon, China (two studies), Indonesia, Mexico, Mozambique, the Philippines, Russia, and Zambia. The diversity of approaches taken in these studies allows the paper to reflect local conditions and priorities and illustrates many important facets of the trade and poverty link. It does, however, limit the ability to draw broader conclusions. Thus an additional study provides a 15-country cross-section analysis, and a global analysis provides estimates for the world as a whole. "--World Bank web site